Effect of High-Quality Whole-Course Care on Psychological Status and Postoperative Pharyngeal Complications in Patients Undergoing Surgery for Hyperparathyroidism Secondary to Chronic Rrenal Failure - Luo, Qinghong; Zheng, Shuquan (Frontiers in Surgery, 2022)
Objective. To observe the effects of high-quality whole-course care on the psychological status and postoperative pharyngeal complications in patients undergoing surgery for secondary hyperparathyroidism (SHPT) to chronic rrenal failure (CRF). Methods The clinical data of 62 patients who underwent surgical treatment for CRF-SHPT from April 2018 to October 2021 in our department were retrospectively analyzed and divided into two groups according to receiving high-quality whole-course care (n=33) and routine care after admission (n=29). Compliance, occurrence of pharyngeal complications, improvement of preoperative and postoperative psychological status, nursing satisfaction scores, and serum hormone levels were compared between the two groups. Results The differences between the general conditions and clinical characteristics of the two groups were not significant (P > 0.05). After care, the number of cases with good compliance in the high-quality group was higher than that in the regular group, and the number of cases with non-compliance was lower than that in the regular group (P < 0.05); the difference in the number of cases with partial compliance after care between the two groups was not significant (P > 0.05). There was no significant difference in the incidence of pharyngeal complications such as sore throat, nausea and vomiting, dry throat and hoarseness between the two groups (P > 0.05); however, the 24-h postoperative sore throat and dry throat scores in the high-quality group were significantly lower than those in the regular group (P < 0.05). Patients in the high-quality group had higher nursing attitude, nursing skills, nursing safety, nursing quality, and overall nursing satisfaction scores than the regular group (P < 0.05). Compared with the pre-care period, SAS and SDS scores decreased in both groups after care, and SAS and SDS scores decreased more in the high-quality group than in the regular group (P < 0.05). Conclusion Through the high-quality whole-course care, full informed participation and active cooperation of CRF-SHPT patients, close medical and nursing collaboration, attention to detail and overall level of treatment can effectively improve patient compliance, psychological status and postoperative serum indicators, promote patient recovery and improve nursing satisfaction.